Floridans Amaranten-Garte - Birken, Sigmund von, 1626-1681 (Birken, Sigmund von, 1626-1681. Works. 1988 ;, 2009)
This double volume opens the edition of the posthumous manuscripts of one of the most respected and influential 17th century German authors in his life-time. Vol. 1/I contains the first of Birken's five collections of lyric poetry, the poems of love and friendship composed between 1642 and 1681 - epic poems, songs, sonnets and epigrams covering a wide range of topics and forms, at one and the same time indebted to tradition yet surprisingly modern. They afford multi-faceted insights into the reality of the life in which they were created. Vol. 1/II provides textual variants, printing history.